Whither Flows Beaver Brook? Statistical Estimation of Streamflow Depletion by Groundwater Pumping, and A Policy Evaluation of the Massachusetts Sustainable Water Management Initiative. - Weinberg, Adam. (2017)
Abstract: The Massachusetts Sustainable Water Management Initiative (SWMI) is a policy framework intended to prevent further degradation of fluvial environments while balancing societal needs for water. The policy has faced criticism from both environmentalists and municipal water suppliers questioning the fairness and effectiveness of the policy. The question addressed by this thesis is whether the SWMI framework can reasonably be expected to accomplish its stated goals. This thesis answers the question in two parts. Part I is a policy evaluation that will summarize the stakeholder critiques and place SWMI in the broader context of modern water management strategies. The research is based on an examination of the literature as well as interviews with policy and stakeholder experts. Part II evaluates the SWMI policy quantitatively. Multivariate regression is used to estimate streamflow depletion by groundwater wells in Beaver Brook, and Billings Brook, in Sharon, MA, and evaluate the potential benefits of SWMI mitigation options. This thesis concludes that SWMI meets the standards set by peer state water management policies and can reasonably be expected to meet its stated goals. The thesis also concludes that multivariate regression is an effective method for estimating streamflow depletion, and is more cost effective and versatile than conventional analytical streamflow depletion modeling methods.; Thesis (M.A.)--Tufts University, 2013.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Scott Horsley.; Committee: Robert Russell, and Brian Thomas.; Keywords: Water resources management, Hydrologic sciences, and Environmental management.